Evaluating the Integration of Agroecological Principles into Kenya's Legal and Policy Framework - Awiti, Alex O.; Ndiwa, Aurillia M. (CIFOR-ICRAF, 2024)
This paper evaluates the integration of three high - level categories of the 13 principles of agroecology — resource efficiency, resilience, and social equity and responsibility — into Kenya's Constitution and 14 sectoral strategies, policies, and laws. Policy, legal, and strategy documents were analyzed to identify enabling and exemplary provisions and barriers to the agroecological transformation of Kenya's food system. Kenya has a raft of laws, policies, and strategies that integrate agroecological principles and support the agroecological transition of the food system. These include provision for: i) integrated soil and plant health; ii) re - design of farms and landscapes through integrated soil, water and management, and the integration of crops, trees and livestock to support farm diversification; iii) enhancing climate resilience; iv) strengthening co-creation of knowledge and ensuring equity through participation of local communities in the food system. The focus on achieving high cereal yields, bolstered by public subsidies for mineral fertilizers and hybrid seeds, limits the investment in agroecological approaches. Despite a raft of enabling and exemplary provisions, uneven distribution of resources and inconsistent implementation present veritable barriers to agroecological transition. More importantly, there is a need to strengthen institutional mechanisms for consultation and cooperation between the national and county governments to ensure the agroecological transformation of food systems nationally.